2012
DOI: 10.1016/j.jns.2012.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the role of the GABRG2 gene variant in migraine

Abstract: Migraine is the most common neurological disorder worldwide affecting about 12% of the worldwide population. This disorder has been classed into two main types of migraine-with and without aura. While a number of factors can influence the onset of migraine, a major factor is that of genetics. The GABAA gene encodes for the GABAA receptor. Along with other receptors, the GABAA receptor is involved in the mediation of neuronal activities. In this study, a GABRG2 gene (GABAA receptor gamma-2-subunit) SNP (rs21103… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, the possible contribution of genetic polymorphisms related to GABR genes in the risk for migraine is not well established, and, moreover, none of them have shown association in GWAS . Following the identification of susceptibility loci for familial migraine in two genomic regions containing certain subtypes of GABR genes at the chromosomes 15q11‐q13 and Xq24‐q26, the results of the majority of case‐control studies looking for the possible association of between SNPs in these genes and the risk for migraine showed lack of association, and other study on a unique SNP in the GABRG2 failed to find association as well . There is only one report describing association between several SNPs in the GABRQ , GABRE , and GABRA3 genes, and even gene‐gene interaction between these SNPs and the risk for migraine, but the results of this study, based on a sample of low size, require further confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the possible contribution of genetic polymorphisms related to GABR genes in the risk for migraine is not well established, and, moreover, none of them have shown association in GWAS . Following the identification of susceptibility loci for familial migraine in two genomic regions containing certain subtypes of GABR genes at the chromosomes 15q11‐q13 and Xq24‐q26, the results of the majority of case‐control studies looking for the possible association of between SNPs in these genes and the risk for migraine showed lack of association, and other study on a unique SNP in the GABRG2 failed to find association as well . There is only one report describing association between several SNPs in the GABRQ , GABRE , and GABRA3 genes, and even gene‐gene interaction between these SNPs and the risk for migraine, but the results of this study, based on a sample of low size, require further confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Fernández et al showed lack of association between common SNPs in these genes and the risk for migraine in a case‐control association study, which included GABRE3 rs2050843 (192 cases/142 controls), GABRE5 rs2256882 (177 cases/135 controls), a GABRE9 novel SNP (158 cases/100 controls), and GABRQ rs8810652 (202 cases/155 controls), and a trend toward a nonsignificant increased frequency of the GABRQ rs8810652TT genotype in patients with MWoA compared with those with MWA. In contrast, Quintas et al, in other case‐control association study involving 153 cases and 217 controls, described increased risk for migraine in carriers of the GABRQ rs3810651AT genotype, and in males carrying the allele T of the GABRE rs5925077 variant or the allele C of the GABRA3 rs2201169 variant; and decreased risk in carriers of the GABRA3 rs3902802CT and GABRA3 rs2131190GA genotype, while they found no association with other tagging SNPs in the GABRA3 , GABRQ , and GABRE genes. Chen et al described lack of association between the GABRG2 rs211037 variant and the risk for migraine in a case‐control association study involving 245 patients and 247 controls. Finally, Plummer et al described a down regulation in the expression of mRNA of the GABRA3 and GABBR2 genes, and normal expression of the mRNA of the GABRB3 and GABRQ genes, in peripheral blood leukocytes of 28 migraneurs compared with 22 controls.…”
Section: Biochemical Pharmacological Neurophysiological and Experimentioning
confidence: 99%
See 1 more Smart Citation
“…Two association studies exploring that hypothesis did not find any convincing evidence [46,47]. Also, Chen et al investigated the role of one SNP in GABRG2 gene located on chromosome 5q31.1-q33.1, but no significant differences in allele frequencies were found [48]. An Australian study [24] focused on candidate genes in the X-chromosome ( GABRE, GABRQ ) and their involvement in migraine but no association was found with the SNPs tested.…”
Section: Discussionmentioning
confidence: 99%
“…Due to neurological origin of migraine, some researchers have studied receptors involved in mediation of neuronal activities. Chen et al [2] characterized one polymorphism in GABRG2 gene encoding the GABAA receptor gamma-2-subunit (rs211037) on a migraine case–control population of 546 subjects. No significant correlation was found.…”
Section: Reviewmentioning
confidence: 99%